A Comparative Survey Study of In-Person Versus Virtual Trauma Peer Review Meetings. Issue 4 (July 2022) - Zebley, James A.; Chang, Parker; Sarani, Babak; Boese, Stephanie; Messing, Jonathan
Abstract : Background: The American College of Surgeons Committee on Trauma mandates regular peer review meetings for verified trauma centers. The COVID-19 pandemic forced in-person meetings to transition to an online platform. Objective: The objective of this study was to assess the opinions of participants regarding the benefits and negative aspects of the virtual peer review process. We hypothesize that physicians and nurses would prefer a virtual meeting format. Methods: An anonymous online survey of members of the American Association for the Surgery of Trauma and the Society of Trauma Nurses was distributed in May and June of 2021. Demographic data and Likert scale-based responses were collected using the Research Electronic Data Capture platform. Results: Invitations were sent to 1, 726 physicians and 2, 912 nurses. In total, 137 (8%) physicians and 141 (5%) nurses completed the survey. Both groups felt that either platform was effective in addressing opportunities for improvement in care. Physicians disagreed with the statement that anonymous online voting improved their ability to more accurately address opportunities for improvement. In total, 108 (79%) physicians and 100 (71%) nurses preferred a hybrid meeting. Only 18 (13%) physicians and 23 (16%) nurses wanted virtual meetings, whereas only 29 (21%) physicians and 36 (26%) nurses wanted in-person meetings going forward. Conclusions: Virtual and in-person trauma peer review meetings are equally effective in terms of case discussion and identifying opportunities for improvement in care. Given that most people preferred a hybrid meeting, future studies evaluating how best to incorporate and implement this format are needed.